Probing Multivalent Carbohydrate-Protein Interactions With On-Chip Synthesized Glycopeptides Using Different Functionalized Surfaces - Tsouka, Alexandra; Hoetzel, Kassandra; Mende, Marco; Heidepriem, Jasmin; Paris, Grigori; Eickelmann, Stephan; Seeberger, Peter H.; Lepenies, Bernd; Loeffler, Felix F. (Frontiers in Chemistry, 2021)
Multivalent ligand–protein interactions are a commonly employed approach by nature in many biological processes. Single glycan–protein interactions are often weak, but their affinity and specificity can be drastically enhanced by engaging multiple binding sites. Microarray technology allows for quick, parallel screening of such interactions. Yet, current glycan microarray methodologies usually neglect defined multivalent presentation. Our laser-based array technology allows for a flexible, cost-efficient, and rapid in situ chemical synthesis of peptide scaffolds directly on functionalized glass slides. Using copper(I)-catalyzed azide–alkyne cycloaddition, different monomer sugar azides were attached to the scaffolds, resulting in spatially defined multivalent glycopeptides on the solid support. Studying their interaction with several different lectins showed that not only the spatially defined sugar presentation, but also the surface functionalization and wettability, as well as accessibility and flexibility, play an essential role in such interactions. Therefore, different commercially available functionalized glass slides were equipped with a polyethylene glycol (PEG) linker to demonstrate its effect on glycan–lectin interactions. Moreover, different monomer sugar azides with and without an additional PEG-spacer were attached to the peptide scaffold to increase flexibility and thereby improve binding affinity. A variety of fluorescently labeled lectins were probed, indicating that different lectin–glycan pairs require different surface functionalization and spacers for enhanced binding. This approach allows for rapid screening and evaluation of spacing-, density-, ligand and surface-dependent parameters, to find optimal lectin binders.